Applying the community readiness model to identify and address inequity in end-of-life care in South Asian communities. (April 2023) - Moss, Rachael H; Hussain, Jamilla; Islam, Shahid; Small, Neil; Dickerson, Josie
Background: Individuals from minoritised ethnic backgrounds are less likely than individuals from the dominant ethnic group to access palliative care services and to have documented Advance Care Plans. They are more likely to be admitted to hospital in the last months of life. Aim: To use the Community Readiness Model to identify the barriers that influence how South Asian communities access and use two new palliative care services. Design: The Community Readiness Model is a validated tool that measures the readiness of a community. Key stakeholders were asked to: (i) complete a questionnaire to assess South Asian communities' readiness to engage in advance care planning and, (ii) attend a focus group to explore their views on the communities' understandings of palliative and end-of-life care. Setting/participants: Ten key stakeholders who held a variety of occupations within palliative and end-of-life care services were recruited from the community. Findings: The South Asian communities were found to be at the 'pre-planning' stage of readiness, despite initiatives to improve awareness. The readiness of the health system was found to be limited, with a narrow medical focus during advance care planning, poor integration of voluntary and community services and limited understanding of what people consider a 'good' death. Conclusions: The Community Readiness Model allowed insight into the South Asian communities' awareness of and readiness (to use) palliative care services. Using the Community Readiness Model before service implementation allowed steps to be taken to avoid widening inequities in access and use of new services.